The Tol-Pal System of Uropathogenic Escherichia coli Is Responsible for Optimal Internalization Into and Aggregation Within Bladder Epithelial Cells, Colonization of the Urinary Tract of Mice, and Bacterial Motility - Hirakawa, Hidetada; Suzue, Kazutomo; Kurabayashi, Kumiko; Tomita, Haruyoshi (Frontiers in Microbiology, 2019)
Urinary tracts infection (UTI) caused by uropathogenic Escherichia coli (UPEC) is a common infectious disease. With the shortage of new antimicrobial agents, the increase in UPEC resistance to commonly used drugs, such as fluoroquinolones and -lactams including carbapenems is a critical issue. UPEC invades urinary tract cells, where it aggregates, and subsequently, forms biofilm-like multicellular colonies termed intracellular bacterial communities (IBCs). This process allows the bacteria to establish infections and so may be a good potential target for new drugs to treat infections. Here, we show that deletion of the tolB gene, encoding a protein of the Tol-Pal system that was originally characterized as a protein complex for colicin uptake and maintenance of the outer membrane, decreases the level of bacterial internalization into and aggregation within cultured bladder epithelial cells and also inhibits the colonization of mice urinary tracts. The tolB mutant also exhibited defective motility because of impaired flagellum syntheses. The fliC and motA mutants, which are non-motile strains, also exhibited lower levels of bacterial internalization and aggregation than their wild-type parent. Additional deletion of tolB in the fliC mutant did not further decrease these, suggesting that the attenuated virulence of the tolB mutant is a result of defective motility. The tolA, tolQ, tolR and pal mutants that lack other members of the Tol-Pal system also exhibited lower levels of motility and aggregation within bladder epithelial cells compared to their wild-type parent. These combined results suggest another role of the Tol-Pal system, i.e., that it is responsible for optimal internalization, aggregation followed by IBC formation within urinary tract cells, and bacterial motility.